Correction: Biochemical and structural characterization of the human gut microbiome metallopeptidase IgAse provides insight into its unique specificity for the Fab’ region of IgA1 and IgA2 - Ramírez-Larrota, Juan Sebastián; Juyoux, Pauline; Guerra, Pablo; Eckhard, Ulrich; Gomis-Rüth, F. Xavier (PLOS Pathogens, 2025)
null